Determination of Corrosion in an X65 grade CO2-H2S-Brine-Api Steel System using a Rotary Cylinder Electrode (2010)
By using Linear Polarization Resistance, Electrochemical Impedance Spectroscopy and Tafel Extrapolation, the corrosion resistance of a carbon steel API 5L X65 degree was evaluated in the Rotating Cylinder Electrode (RCE), submerged in a 3%p NaCl solution deareated and 40 ºC at atmospheric pressure. The dynamics of tests was controlled by the RCE with speeds between 0 and 3 m/s, and varying the H2S/CO2 molar relation from 0 to 8.34x10-3. The mass transference coefficients of H+, HS- and HCO3- and the shear stress near the interface metal-liquid interface were determined, by using applicable experimental correlations for the geometry of RCE. Finally, correlations were determined which showed the relationship between the corrosion rate and the mass transference coefficients and shear stress, with the fluid flow of this multiphase system and the H2S/CO2 molar ratio.